6n+.2=4n+.6

Simple and best practice solution for 6n+.2=4n+.6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6n+.2=4n+.6 equation:



6n+.2=4n+.6
We move all terms to the left:
6n+.2-(4n+.6)=0
We add all the numbers together, and all the variables
6n-(4n+0.6)+.2=0
We add all the numbers together, and all the variables
6n-(4n+0.6)+0.2=0
We get rid of parentheses
6n-4n-0.6+0.2=0
We add all the numbers together, and all the variables
2n-0.4=0
We move all terms containing n to the left, all other terms to the right
2n=0.4
n=0.4/2
n=0.4/2

See similar equations:

| (3x+50=2x+8) | | 7h=15.4 | | x/5=19.5 | | 25y=25y+75 | | .15(x+6.2)=107.27 | | -16=-4(2+4x)-2(7x+4) | | 2x/40=5/4x | | .15x+.93=107.27 | | 2x+6(1/6)=1 | | 100=x130 | | 2w+2(w+4.75)=129.5 | | 5x-2.6=x+8.2 | | -6(-2x+4)+2(x+6)=72 | | 4(.25+c)=1.8 | | 2x-5x-65=35 | | 12.5=a+5.5 | | 515+c=223 | | 15x/12=16÷24 | | x-0.23x=50000 | | (H-x)^3-3(H-x)(K-S*x)^2+2(K-S*x)^3=0 | | 2(6r+5)=14-(7r-4)+11r | | 5(-1/9)+8y=-5 | | 14+13y=20y-2 | | 4(5y=2)=48 | | 1/9+3y=24 | | 0.9v-30.61=3.5(0.8+7.6v) | | 8x+4(1.5x)=800 | | x+6/4=3 | | 1.5x-x=0.x-1.2 | | x+9/9=-3 | | 8*x+20-(6*x+18)=0 | | 2(6w-1)=8w |

Equations solver categories